Light-Induced Agglomeration and Diffusion of Different Particles with Optical Tweezers - 李雪璁 孙秀冬 刘鸿鹏 张建隆 (Chinese physics letters, 2010)
The dynamic process of light-induced agglomeration of carbon nanotubes （CNTs）, C60 and Escherichia coli （E.eoli） in aqueous solutions is demonstrated using an optical tweezers system. Based on the results, the diameter of the agglomerated region and the agglomeration rate increase with the increasing laser power. After the saturation-stable period, CNTs diffuse completely, C60 clusters only diffuse partially, and E. coli never diffuses in the agglomeration region. Theoretical analyses show that the molecular polarization and thermal diffusion of particles play crucial roles in the diffusion process. The and sort nanoparticles. results indicate the possibility of using light to aggregate